Social evolution: the decline and fall of genetic kin recognition. - Gardner, A; West, SA (2007)
Animals should benefit from the ability to recognise their kin, yet curiously this faculty is often absent. New theory confirms that genetic kin recognition is inherently unstable, explaining its rarity.